Rumah Kreatif Tambak Bayan; Arts Community Based Character Education - Sari, Melati Pravita; Rifandi, Ilham; Rahmatika, Aulia (Institut Seni Indonesia Padangpanjang, 2024)
This research uses qualitative methods to understand conditions in the field in a real and clear manner. This article reviews the significant role played by Tambak Bayan Creative House (RKTB) in character education for its participants, especially children from low economic backgrounds and academic challenges. RKTB provides a platform for participants to develop their creativity through various arts and cultural activities. His character education program not only enhances artistic abilities, but also teaches values such as cooperation, honesty, and respect, which are important for an individual's holistic development. The evaluation results show a significant increase in the academic achievement and personal development of RKTB participants, reflected in increased learning motivation and the ability to express themselves creatively. This article concludes that RKTB is not only a center for creativity, but also an environment that builds positive character and helps participants to grow as valuable individuals in society